An Unusual Prenatal Ultrasound Image of Placental Lake in High Risk Pregnancy - Bursac, D; Kulas, T; Madzarac, V; Kardum, V; Skrtic, A; Hrgovic, Z (Nepal Journal of Obstetrics and Gynaecology, 2014)
No abstract available. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 75-76 DOI: http://dx.doi.org/10.3126/njog.v8i2.9779